Water Quality Index (WQI) Significance and Efficiency as a Measure of Water Quality - Mohammed Y.; Salih G.H.A.; Thiruchelvam S. (Springer Science and Business Media Deutschland GmbH, 2024)
The quality of water is crucial for human health and well-being. The physical, chemical, and microbacterial water quality criteria are included within the assessment process for the Water Quality Index (WQI) method. In fact, water utilities have always had trouble finding suitable management and administration procedures to ensure high-quality water. A clear and efficient technique that may be applied to immediately evaluate water quality condition is needed to offer a response. The study's inquiry is whether WQI is sufficient for water assessment in terms of quality? An investigation was carried out into the available existing studies based on the objectives that were planned to define the methods, categorize the assessment areas, type of water sources, and assessment boundaries. The study results have declared the significance of WQI implementation as an assessment indicator to assist immediate decision-making on water source quality control. Nevertheless, up to 66% of the selected studies employed other index measures to support the assessment process. For instance, theWater Stability Index (WSI) is targeted to assess chemical and physical parameters, while Comprehensive Pollution Index (CPI), Metal Index (MI), and Contamination Index (CI) are targeted to determine the level of pollution. The Hazard Index (HI) is oriented to assess human health risks. The study has noted the variation in rating grades and values within the same index, which could lead to conflict when scaling different projects of the same type. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.